Late Ancient Nora: Ongoing Researches in the NW Area (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The paper presents the data of a limited archaeological digging in the area behind the apodyterium wall of the Small Baths in Nora. It has been possible to highlight five phases: the two more ancient ones attest a residential purpose of the area. The subsequent phases document the use of this place as a discharge area especially of building material. Noteworthy is the discovery of several fragments of frescoed plaster from one or more surrounding monuments. All phases are to be referred to a narrow time span, between the end of the fourth and fifth centuries AD.